Effect of Feeding Bypass Fat and Unprotected Oil on Feed Intake, Digestibility and Production Performance in Lactating Crossbred Cows - Shankhpal, Sachin; Gupta, R.S.; Parnerkar, S.; Dhami, A.J. (Indian Journal of Animal Nutrition, 2018)
Eighteen lactating crossbred cows (HF Ã— Jersey Ã— Kankrej) yielding 10 to 12 L of milk daily and 7-59 days in milk were divided into three groups of six animals each. The cows under T1 were fed control diet (compound concentrate mixture + dry fodder + green fodder), in T2, control diet + bypass fat supplement (200 g/h/d) and in T3, control diet + unprotected oil (170 g/h/d). There was no difference in DMI, CPI, DCPI and TDNI in the three groups of cows. Ether extract digestibility was higher (P<0.05) in treatments T2 and T3 than T1. The average daily 4% FCM production was 10.80, 12.57 and 12.30 kg per animal in treatments T1, T2 and T3, respectively. Cows in group T2 produced 16.38% more 4% FCM than the cows in group T1. The average milk fat content in treatments T1, T2 and T3 was 4.07, 4.57 and 4.46%, respectively which showed that the bypass fat/oil supplementation in lactating cows (T2 and T3) increased (P<0.05) fat content of milk as compared to that in control diet (T1). The efficiency of feed conversion in terms of DM and nutrients required to produce one kg whole milk and 4% FCM also improved in cows fed bypass fat than the cows fed control diet, though the values were statistically similar in all the treatemnts. The data suggested that cows fed bypass fat produced milk of higher fat content. There was significant (P<0.05) reduction in cost of milk production with improved reproductive performance in cows fed diet supplemented with bypass fat.